Assessment of awareness and attitudes of pregnant women toward labor epidural analgesia and factors influencing the decision to opt for it: A cross-sectional study - Adugna Aregawi Kassa; Wosenyeleh A. Sahle; Tsehaynew Desalew; Zufan Lakew; Tigist Behabtu (PLoS ONE, 2025)
Background Epidural analgesia is one of the most effective forms of pain relief for active first stage and second stages of labor. Despite its many advantages, the technique is not routinely practiced in most centers in developing countries. Awareness and attitudes toward it, as well as the reasons for its limited utilization, have not been explored in our setting. Therefore, the aim of this study was to assess the awareness and attitudes of pregnant women toward labor epidurals and to assess the factors influencing their decision to receive labor epidural analgesia (LEA) during labor and delivery. Methods A cross-sectional study was conducted from June 03 to August 30, 2024 at Hemen Medical Center. A structured questionnaire was used to collect the data. A systematic sampling method was used to collect the data. The collected data were analyzed using SPSS version 26. Descriptive statistics were used to summarize the results, and both bivariate and multivariable logistic regressions were employed to identify factors influencing their decision to receive labor epidural analgesia during labor and delivery. A p-value of < 0.05 was used to determine statistical significance. Results Two hundred thirty pregnant women, with a mean age of 29.9 ± 4.3 years, were included in the analysis. Approximately 78% of the participants had heard of labor epidural analgesia (LEA), although only 6.5% reported healthcare providers as their primary source of information. Approximately 47% believed that LEA was effective for pain relief during labor. However, only 14.3% expressed a willingness to consider using LEA during delivery. Education level, family income, perceived risk to the Fetus, and perceived effectiveness in relieving pain were identified as factors influencing the decision to consider LEA during delivery. Conclusion Despite relatively high basic awareness of LEA, many participants remain hesitant to utilize it during labor and delivery. Comprehensive health education and counselling during antenatal care are essential to address misconceptions and promote informed decision-making regarding LEA.